Effects of land use and land cover change on sediment yield for Upper Sebakwe and Upper Nyazvidzi sub-catchments in Chikomba District - Chiwera, Blessing (Midlands State University, 2017)
The study of the response of sediment yield to land use and land cover changes is quite critical for watershed management and policy formulation. This research investigated the effect of land use and land cover changes to sediment yield from upper Sebakwe and upper Nyazvidzi sub-catchments. Changes in land use and land cover were determined by the use of Landsat Thematic Mapper ™ imagery for years 1984, 1994, 2004 and 2010 using ArcMapTM 10 tool. Sediment yield resulting from the land use and land cover changes was calculated using the Regional Small Catchment Sediment Yield Prediction Model for years 1984, 1994, 2004 and 2010. The effects of changes in land use and land cover to sediment yield were evaluated based on the correlation tested between the parameters. In upper Nyazvidzi sub-catchment, 31.2% of forest area was lost while in upper Sebakwe sub-catchment, there was a loss of 31.3%. Cultivated land increased by 10.9% for upper Nyazvidzi while a slight 0.1% was increased in upper Sebakwe. Pasture land increased by 38.2% and 31% for upper Nyazvidzi and Sebakwe sub-catchments respectively. There was a significant loss of water bodies in upper Nyazvidzi with a reduction by 16.8% while Sebakwe gained by 0.1%. These changes in land use and land cover resulted in significant changes in sediment yield for both sub-catchments. This study proved that land use and land cover changes are usefully correlated to sediment yield in both sub-catchments. These findings are relevant to sub-catchments which are experiencing dynamic land use and land cover changes which often lack measurement. The resultant effects of these changes are of great concern relative to sediment yield which causes siltation of water bodies and loss of watershed integrity in many sub-catchments.